PENTINGNYA MEMAHAMI DAN MENGIMPLEMENTASIKAN NILAI-NILAI PANCASILA DI LINGKUNGAN MASYARAKAT - Himmatul Izza Nur Fadhila; Fatma Ulfatun Najicha (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This study aims to: 1) Provide understanding to the wider community of the principles contained in Pancasila, 2) To educate the public about the importance of implementing Pancasila values in daily activities. This study uses a literature study method that collects various information and facts from several documents related to the research question, namely Pancasila and its implementation in society. As an ideological concept for the nation, Pancasila is formed from the superior values of the Indonesian nation which are the basis of belief in achieving the goals and ideals of the nation. Pancasila contains values or principles that are useful to be applied and implemented in daily activities in the community. As citizens of Indonesia, it is necessary to pay attention to and realize the importance of implementing Pancasila values so that bad things such as conflicts and divisions do not occur. The existence of cases of conflict and division is a result of the lack of awareness of citizens of the importance of Pancasila as a guide to achieve the goals and ideals of the nation.